2000
DOI: 10.1161/01.cir.102.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects on Clinical Outcomes of Aggressive Lowering of Low-Density Lipoprotein Cholesterol Levels and Low-Dose Anticoagulation in the Post Coronary Artery Bypass Graft Trial

Abstract: Background-The Post Coronary Artery Bypass Graft Trial, designed to compare the effects of 2 lipid-lowering regimens and low-dose anticoagulation versus placebo on progression of atherosclerosis in saphenous vein grafts of patients who had had CABG surgery, demonstrated that aggressive lowering of LDL cholesterol (LDL-C) levels to Ͻ100 mg/dL compared with a moderate reduction to 132 to 136 mg/dL decreased the progression of atherosclerosis in grafts. Low-dose anticoagulation did not significantly affect progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
127
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(134 citation statements)
references
References 23 publications
4
127
0
3
Order By: Relevance
“…the higher rate of myopathy with simvastatin 80 mg daily than with 20-40 mg daily 78 ). Combination of precise information about the treatment that is received during a specific period in a randomized trial and prolonged follow-up of outcomes after the trial has ended (perhaps through linkage to electronic health records 96 ) may also allow the reliable assessment of the later effects of the treatment (as has been done for statin therapy [97][98][99][100][101][102][103][104] ) while still avoiding the potential biases that are inherent in observational studies.…”
Section: Potential To Assess Prolonged Exposure To Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…the higher rate of myopathy with simvastatin 80 mg daily than with 20-40 mg daily 78 ). Combination of precise information about the treatment that is received during a specific period in a randomized trial and prolonged follow-up of outcomes after the trial has ended (perhaps through linkage to electronic health records 96 ) may also allow the reliable assessment of the later effects of the treatment (as has been done for statin therapy [97][98][99][100][101][102][103][104] ) while still avoiding the potential biases that are inherent in observational studies.…”
Section: Potential To Assess Prolonged Exposure To Treatmentmentioning
confidence: 99%
“…For example, 5 years of treatment with a statin regimen that lowers LDL cholesterol by 2 mmol/L would be expected to prevent major vascular events in about 1000 (10%) higher-risk patients per 10,000 treated and in about 500 (5%) lower-risk patients per 10,000 treated ( Figure 5; which also provides estimates of the absolute benefits with 1.5 and 1.0 mmol/L LDL-reductions ). 32 The continued follow-up of patients beyond the end of the trials has found that the benefits of statin therapy persist [97][98][99][100][101][102] (and may even become larger 96,103,104 ) for many years after the differences in statin use between the randomized groups have ceased. However, of more relevance for a treatment that is intended to be continued life-long once it has been started, the meta-analyses show that statin therapy reduces the risk of major vascular events during each year that it is continued (Figure 4).…”
Section: Reductions In Rates Of Major Vascular Eventsmentioning
confidence: 99%
“…At the end of the study, the aggressive strategy showed a nonsignificant benefit in the combined clinical end point of death from any cause, MI, cerebral vascular accident, CABG or percutaneous coronary intervention. This benefit became statistically significant during the extended study period (31,32). There are no long-term data for newer, more potent statins such as atorvastatin, although it would be reasonable to assume that they would be at least as effective as the older statins in preventing vein graft disease.…”
Section: Lipid-lowering Therapymentioning
confidence: 99%
“…Após 7,5 anos de evolução, observaram-se reduções de 30% nos procedimentos de revascularização e de 24% nos eventos clínicos 15,23,24 .…”
Section: A -Estudos Controlados Por Angiografiaunclassified